The effect of educational philosophies on learning principles with the mediating role of epistemological beliefs among faculty members of University of Sistan and Baluchestan - sara jenabadi; Vali Mehdinezhad (مطالعات روانشناسی تربیتی)
The aim of this study was to investigate the effect of faculty members'educational philosophies on learning principles with the mediating role of epistemological beliefs.The research method used in this study was descriptive-correlational. The statistical population of the study included the professors of Sistan and Baluchestan University in the academic year 1300-1400 with 341 people and the volume of the sample population was estimated to be 181 based on the sample size determination table of Singh and Masko.The class sampling method was proportional to the volume (according to the faculty) and sampling was available. Data were collected from three questionnaires of Kant's educational philosophies (2004), Sedler and Zeitelman (2013) and Schumer's epistemological beliefs (1993), whose validity was calculated to be 0.84, 0.76 and 0.89, respectively. One-group t-test was used to examine the studied variables, confirmatory factor analysis was used for construct validity and structural equation method was used to test research hypotheses with the help of SPSS20 and Lisrel8 software. The results showed that the effect of the variable of educational philosophies on the principles of learning and epistemological beliefs are 0.59 and 0.52, respectively, and this effect was also significant. Also, the effect of educational philosophies on the principles of learning mediated by epistemological beliefs was 0.11 and this effect was significant; Therefore, the variable of educational philosophies had a positive and significant relationship with the principles of learning and epistemological beliefs. The mediating role of epistemological beliefs in the relationship between educational philosophy and learning principles was also confirmed